DEFINITION OF THE OBJECTS OF MULTIVARIABLE CONTROL OF TECHNOLOGICAL PROCESS OF SMELTING INDUSTRY ON THE BASIS OF OPTIMIZATION MODEL - Koshymbaev, Shamil Koshymbaevich; Shegebaeva, Zhibek; Wójcik, Waldemar (Informatyka, Automatyka, Pomiary w Gospodarce i Ochronie Środowiska, 2014)
This article analyzes work of metallurgical shop as a complex control object. It also includes description of copper complex and synthesizes three-level structure of control system. Technical and economical indexes and also control object are defined in this article.